Marketing management - Kotler, Philip; Keller, Kevin Lane; Chernev, Alexander (Harlow, Essex, United Kingdom Pearson Education Limited, 2022)
The world of marketing is changing every day ― and in order for students tohave a competitive edge, they need a text that reflects the best and mostrecent marketing theory and practices. Marketing Management collectivelyuses a managerial orientation, an analytical approach, a multidisciplinaryperspective, universal applications, and balanced coverage to distinguish itfrom all other marketing management texts out there. Unsurpassed in its breadth,depth, and relevance, the 16th Edition features a streamlinedorganization of the content, updated material, and new examples that reflectthe very latest market developments. After reading this landmark text, studentswill be armed with the knowledge and tools to succeed in the new marketenvironment around them.
PART I: Fundamentals of Marketing Management: 1. Defining Marketing for the New Realities -- 2. Marketing Planning and Management.

PART II: Understanding the Market: 3. Analyzing Consumer Markets -- 4. Analyzing Business Markets -- 5. Conducting Marketing Research.

PART III: Developing a Viable Market Strategy: 6. Identifying Market Segments and Target Customers -- 7. Crafting a Customer Value Proposition and Positioning.

PART IV: Designing Value: 8. Designing and Managing Products -- 9. Designing and Managing Services -- 10. Building Strong Brands -- 11. Managing Pricing and Sales Promotions.

PART V: Communicating Value: 12. Managing Marketing Communications -- 13. Designing an Integrated Marketing Campaign in the Digital Age -- 14. Personal Selling and Direct Marketing.

PART VI: Delivering Value: 15. Designing and Managing Distribution Channels -- 16. Managing Retailing.

PART VII: Managing Growth: 17. Driving Growth in Competitive Markets -- 18. Developing New Market Offerings -- 19. Building Customer Loyalty -- 20. Tapping into Global Markets -- 21. Socially Responsible Marketing
Global edition.
Includes bibliographical references (pages 513-573) and indexes.
Keywords: Marketing -- Management